2021
DOI: 10.21037/tp-21-445
|View full text |Cite
|
Sign up to set email alerts
|

Development and verification of a risk prediction model for bronchopulmonary dysplasia in very low birth weight infants

Abstract: Background: To analyze the risk factors of bronchopulmonary dysplasia (BPD) of very low birth weight infants (VLBWIs), and to develop and verify a risk prediction model of BPD. Methods: The data of 611 VLBWIs from the neonatal intensive care unit (NICU) of a tertiary grade A hospital in Suzhou from January 2017 to September 2019 were collected. The data was randomly divided into the modeling set (451 cases) and the validation set (160 cases). Binary logistic regression was used to analyze the data, and the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…The present study found that infants with history of neonatal asphyxia are at high risk of developing BPD, and this nding is consistent with the results of previous studies [21,22]. For infants with small GA and low birth weight, the immature lung development and di culty in postoperative respiratory establishment can easily lead to asphyxia and resuscitation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study found that infants with history of neonatal asphyxia are at high risk of developing BPD, and this nding is consistent with the results of previous studies [21,22]. For infants with small GA and low birth weight, the immature lung development and di culty in postoperative respiratory establishment can easily lead to asphyxia and resuscitation.…”
Section: Discussionsupporting
confidence: 93%
“…The occurrence of NRDS results in increased pulmonary surfactant consumption, leading to high ventilation pressures, oxygen concentrations, and lung injury to some extent. In the current study, the presence of NRDS is shown to be associated with increased risk of BPD [21], indicating that surfactant therapy should be given as early as possible to promote lung maturation.…”
Section: Discussionmentioning
confidence: 67%
“…A total of 1,011 articles were retrieved from the databases using systematic and manual searches. After removing the duplicates, and performing screening of abstracts and full-text articles, 21 studies (5,15,16,19,20,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) were included. These studies included a total of 6,567 control infants and 1,476 patients with BPD, and were eligible for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Given the hypoplastic state of the smooth muscle and the lack of intimal cushion, an immature ductus arteriosus might not close timely after birth, causing enhanced blood flow to the lungs, pulmonary edema, lung congestion, and subsequent exacerbation of pulmonary inflammation, declining lung function, and reduced gas exchange. Although the precise role of PDA in BPD onset and progression remains elusive, the risk of BPD in premature infants with PDA was found to be 6.266 times that of non-PDA counterparts, with the BPD risk escalating alongside PDA shunt volume and duration [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%